Efficacy of cognitive rehabilitation on psychosocial functioning in Borderline Personality Disorder: a randomized controlled trial. Issue 1 (December 2015) - Pascual, Juan; Palomares, Nerea; Ibáñez, Ángela; Portella, Maria; Arza, Rocío; Reyes, Raquel; Feliu-Soler, Albert; Díaz-Marsá, Marina; Saiz-Ruiz, Jerónimo; Soler, Joaquim; Carrasco, Jose
Abstract Background Follow-up studies revealed that subjects with borderline personality disorder (BPD) present high rates of clinical remission, although psychosocial functioning often remains impaired. The aim of this study is to evaluate the efficacy of a cognitive rehabilitation intervention versus a psychoeducational program on psychosocial functioning in subjects with BPD. Methods A multicenter, randomized, and positive-controlled clinical trial was conducted. Seventy outpatients with BPD were randomized to cognitive rehabilitation or psychoeducational group interventions. Participants were evaluated after completion of the intervention period (16 weeks) and after the follow-up period (6 months). Psychosocial functioning, clinical and neuropsychological outcomes were evaluated. Results No main effects of group or group x time were observed on functionality but a significant effect of time was found.Post-hoc analyses showed that only cognitive rehabilitation increased psychosocial functioning significantly at endpoint. Psychoeducation showed a significant enhancement of depressive symptoms. Conclusions Cognitive rehabilitation and psychoeducational interventions appeared to show good efficacy in improving disabilities in daily life in subjects with BPD. These interventions are easily implemented in mental health settings and have the advantage of improving general functioning and clinical symptoms. Trial registration Clinicaltrials.gov:NCT02033044 . Registered 9 January 2014